Body composition of elite Olympic combat sport athletes - Reale, R.; Burke, L. M.; Cox, G. R.; Slater, G. (European Journal of Sport Science, 2020)
Physique traits of a range of elite athletes have been identified; however, few detailed investigations of Olympic combat sports (judo, wrestling, taekwondo and boxing) exist. This is surprising given the importance of body composition in weight category sports. We sought to develop a descriptive database of Olympic combat sport athletes, compare variables relative to weight division and examine differences within and between sports. Additionally, we investigated the appropriateness of athletes` self-selected weight classes compared to an internationally recognised classification system (the NCAA minimum wrestling weight scheme used to identify minimum `safe` weight). Olympic combat sport athletes (56m, 38f) had body mass (BM), stretch stature and dual-energy X-ray absorptiometry derived body composition assessed within 7-21 days of competition. Most athletes were heavier than their weight division. Sport had an effect (p < .05) on several physique traits, including; lean mass, lean mass distribution, stretch stature and BMI. BM was strongly positively correlated (r > 0.6) with; fat free mass, fat mass and body fat percentage, however, was not predictive of total mass/weight division. The Olympic combat sports differ in competitive format and physiological requirements, which is partly reflected in athletes` physique traits. We provide reference ranges for lean and fat mass across a range of BM. Lighter athletes likely must utilise acute weight loss in order to make weight, whereas heavier athletes can potentially reduce fat mass.